User Interface and User Experience Design of a Tourism Information System for Bima Regency - Moch Ihsan Ramadhani; Jefree Fahana (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2026)
Bima Regency has diverse tourism potential, including natural, cultural, historical, and marine tourism, supported by accommodation and tourism businesses. However, tourism information is still distributed across several platforms, is not centralized, and is not presented completely. This condition makes it difficult for local communities and tourists to obtain information about destinations, facilities, road access, accommodation, events, and tourism news. This study aims to design the UI/UX of a web-based tourism information system for Bima Regency using the Design Thinking method. The research stages include empathize, define, ideate, prototype, and testing. Data were collected through interviews with the Bima Regency Tourism Office and 20 respondents, then analyzed using empathy maps, user personas, affinity diagrams, How Might We, site maps, user flows, and prototype design using Figma. The prototype was evaluated using the System Usability Scale (SUS) with 56 respondents. The resulting prototype includes destination, event, news, accommodation, detailed tourism information, and admin pages for managing tourism content. The SUS test produced an average score of 84.55, categorized as acceptable, grade B, and an excellent adjective rating. These results indicate that the UI/UX design has good usability and can be used as a reference for developing a tourism information system in Bima Regency.